Recent updates in applications of nanomedicine for the treatment of hepatic fibrosis - Setyawati, Damai Ria; Sekaringtyas, Fransiska Christydira; Pratiwi, Riyona Desvy; Rosyidah, A’liyatur; Azhar, Rohimmahtunnissa; Gustini, Nunik; Syahputra, Gita; Rosidah, Idah; Mardliyati, Etik; Tarwadi; El Muttaqien, Sjaikhurrizal (Beilstein journal of nanotechnology, 2024)
Over recent decades, nanomedicine has played an important role in the enhancement of therapeutic outcomes compared to those of conventional therapy. At the same time, nanoparticle drug delivery systems offer a significant reduction in side effects of treatments by lowering the off-target biodistribution of the active pharmaceutical ingredients. Cancer nanomedicine represents the most extensively studied nanotechnology application in the field of pharmaceutics and pharmacology since the first nanodrug for cancer treatment, liposomal doxorubicin (Doxil ® ), has been approved by the FDA. The advancement of cancer nanomedicine and its enormous technological success also included various other target diseases, including hepatic fibrosis. This confirms the versatility of nanomedicine for improving therapeutic activity. In this review, we summarize recent updates of nanomedicine platforms for improving therapeutic efficacy regarding liver fibrosis. We first emphasize the challenges of conventional drugs for penetrating the biological barriers of the liver. After that, we highlight design principles of nanocarriers for achieving improved drug delivery of antifibrosis drugs through passive and active targeting strategies.